A Partnership with Africa How the European Investment Bank delivers on EU policies in Africa and our future plans for development and partnership across the continent - European Investment Bank (European Investment Bank, 2021)
Africa is embarking upon a period in which its political, economic and social outlook will transform. The European Investment Bank is a key part of the EU toolbox that for decades has helped make the partnership between Africa and Europe stronger. We aim to maximise our potential as the EU bank, so that we can join our African partners in addressing today's critical challenges together and embrace our opportunities. This publication lays out our track record in Africa and our vision for our future partnership with the continent.